Strategi Public Relations Pesantren Sidogiri dalam Membangun Citra Lembaga Pendidikan Islam - Chusnul Chotimah (Postgraduate Studies of Universitas Islam Negeri Sunan Ampel Surabaya, Indonesia, 2012)
Pesantren has been believed to be a form of indigenous educational system in Indonesia. The history and nature of pesantren have both shown that there is a good relation between pesantren and the society. This will be the focus of the study. It would investigate the notion of how pesantren is related to the wider community, and what are its strategies to keep the community in touch with it? All this will be discussed with referring particularly to the case of pesantren Sidogiri and its already-existing unit called public relation unit. Qualitative in its nature, the paper is phenomenological in its approach. It assumes that generally speaking, any pesantren in Indonesia would ?in the beginning- run by accident, and not by design. But as it grows, it becomes as modern as any advanced educational institution would be. Hence, the paper will show that pesantren Sidogiri is aware of the importance of imagebuilding, and that it consciously pursues it through its software and hardware mechanism. The paper will also show that the surrounding community and the alumni are in fact part of the pesantren?s network to build a better image.